Ventriculoperitoneal Shunt Surgery in Pediatrics: Does Preoperative Skin Antisepsis with Chlorhexidine/Alcohol Reduce Postoperative Shunt Infection Rate? - Ammar, Ahmed Shawky; Elnoamany, Hossam; Elkholy, Hany (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background In pediatrics, shunt infection is considered the most common complication of ventriculoperitoneal (VP) shunt insertion and the main cause of shunt failure. Careful surgical technique and hygienic skin preparations are highly important for prevention of shunt infections. Our objective was to assess the significance of using preoperative chlorhexidine/alcohol as a skin antiseptic in reducing the infection rate in pediatric VP shunts surgery.Methods We conducted a retrospective, case control study of 80 pediatric patients with active hydrocephalus. The control group (a single step of preoperative skin antisepsis using povidone-iodine and isopropyl alcohol) comprised 40 patients who underwent a shunt surgery between January 2019 and June 2020 and the study group (two steps of preoperative skin antisepsis using 2% chlorhexidine gluconate in 70% isopropyl alcohol as a first step followed by povidone-iodine as a second step) comprised 40 patients who underwent a shunt surgery between July 2020 and January 2022.Results Shunt infection was encountered in 11 (13.7%) patients. It was significantly higher in preterm babies (p = 0.010), patients with a previous shunt revision (p < 0.001), and those with a previous shunt infection (p < 0.001). The incidence of infection was 22.5% in the control group and 5% in study group, with a statistically significant difference (p = 0.023).Conclusions Two steps of preoperative skin antisepsis, first using chlorhexidine/alcohol and then povidone-iodine scrub solution, may significantly reduce the infection rate in pediatric VP shunt surgeries.
Keywords: hydrocephalus; ventriculoperitoneal shunt; pediatrics shunt infection; chlorhexidine gluconate; skin antisepsis